Modulation of gastrointestinal vagal neurocircuits by hyperglycemia - Browning, Kirsteen (Frontiers in Neuroscience, 2013)
Glucose sensing within autonomic neurocircuits is critical for the effective integration and regulation of a variety of physiological homeostatic functions including the co-ordination of vagally-mediated reflexes regulating gastrointestinal (GI) functions. Glucose regulates GI functions via actions at multiple sites of action, from modulating the activity of enteric neurons, endocrine cells, and glucose transporters within the intestine, to regulating the activity and responsiveness of the peripheral terminals, cell bodies and central terminals of vagal sensory neurons, to modifying both the activity and synaptic responsiveness of central brainstem neurons. Unsurprisingly, significant impairment in GI functions occurs in pathophysiological states where glucose levels are dysregulated, such as diabetes. A substantial obstacle to the development of new therapies to modify the disease, rather than treat the symptoms, are the gaps in our understanding of the mechanisms by which glucose modulates GI functions, particularly vagally-mediated responses and a more complete understanding of disease-related plasticity within these neurocircuits may open new avenues and targets for research.